PERANAN PERSONAL HYGIENE DALAM MENINGKATKAN KUALITAS MAKANAN DI RESTAURANT HOTEL KARTIKA WIJAYA BATU - Muhammad Danang Setioko (Universitas Merdeka Malang, 2016)
The purpose of this study was to clarify the role of personal hygiene in improving the quality of food at the Restaurant Hotel Kartika Wijaya. This research is a descriptive study using a qualitative approach . The population in the study of 10 respondents. Data collection techniques were used that observation and questionnaires. Data from the research showed that many employees in the kitchen at the Hotel Kartika Wijaya not apply personal hygiene. Therefore contributes to the quality of food at the Restaurant Hotel Kartika Wijaya .